Hybridized teacher education programs in NYC: A missed opportunity? - Mungal, Angus Shiva (Education Policy Analysis Archives, 2015)
This qualitative study describes the development of hybrid teacher preparation programs that emerged as a result of a “forced” partnership between university-based and alternative teacher preparation programs in New York City. This hybrid experiment was a short-lived, yet innovative by-product of a somewhat pragmatic arrangement between Teach for America, NYC Teaching Fellows and various universities to meet state requirements for credentialization. The institutions benefited from the arrangement but noteworthy here is the documentation of how the teacher education programs informed each other and potentially created a richer educational experience for teacher candidates than either of the programs had alone. With the development of Relay, a stand-alone, alternate graduate school, the partnership, despite its early promise, was ended. With all of its challenges, this forced partnership was characterized by creative and competitive tensions, rather than what ultimately became two parallel teacher education systems largely isolated and in competition with each other.